Oxygen and hydrobiological profiles of homemade manure-based tea in North Africa - Miliani Djezzar; Zakia Kaci; Ibrahim Yahiaoui; Crystele Leauthaud (Scientific Reports)
Abstract Homemade manure tea (HMT) is commonly used in North Africa to enhance crop yields. Yet their physicochemical and biological characteristics remain poorly understood. This study evaluated oxygen and hydrobiological profiles of three types of HMT (bovine, ovine and poultry based, respectively noted HMTb, HMTo, HMTp) and compared them to control solutions of water and water supplemented with soluble NPK fertilizer. For these three types of HMT, oxygen and hydrobiological profiles were measured daily over a 7-day incubation period in three repeated, identical experiments, each comprising randomized treatments and five repetitions per treatment. Our results show that all HMT types rapidly transitioned to hypoxic conditions in the first 24h, shifting to anoxia between day 2 and day 7 depending on HMT type. This anoxic environment promoted denitrification and led to elevated NH4 + concentrations, suggesting the presence of anammox and microaerobic processes. Particulate organic matter contents and bacterial densities were highest in HMTp, while ciliate densities were highest in HMTb. These findings underscore the bioactive potential of HMT as fertilizers, with HMTp showing a favorable nitrogen profile beneficial for agricultural applications. To maintain aerobic conditions longer and reduce nitrogen losses and greenhouse gas emissions, we recommend passive or mechanical aeration, applying HMT during cooler hours, and stabilizing the pH of HMT. This study offers valuable insights to refine HMT preparation protocols, enhancing their use as bioactive fertilizers.